1967
DOI: 10.1071/zo9671173
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of Sminthurus viridis (L.) (Collembola). I. Processes influencing numbers in pastures in Western Australia

Abstract: The changes in numbers of Sminthurus viridis (Collembola: Sminthuridae) in pastures in Western Australia were studied for 9 years on one site and for shorter periods on other sites. Five factors affecting numbers are described: (1) weather, (2) soil type (3) botanical composition of the pasture, (4) predation by Bdellodes lapidaria (Acarina: Bdellidae), and (5) eating of dead bodies by newly hatched nymphs. Weather is generally favourable for the active stages during autumn, winter, and spring. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 0 publications
1
45
0
Order By: Relevance
“…Because B. lapidaria is considered to play an important role in determining S. viridis population size (Wallace 1967), another more detailed Tasmanian survey was begun after population studies on the north-west coast during 1976 suggested that B. lapidaria might be limited in its ability to control populations of S. viridis in this area (Ireson unpub. data).…”
Section: Introductionmentioning
confidence: 99%
“…Because B. lapidaria is considered to play an important role in determining S. viridis population size (Wallace 1967), another more detailed Tasmanian survey was begun after population studies on the north-west coast during 1976 suggested that B. lapidaria might be limited in its ability to control populations of S. viridis in this area (Ireson unpub. data).…”
Section: Introductionmentioning
confidence: 99%
“…viridis Emergence. Although the timing of S. viridis emergence from diapause eggs is variable, it also may be potentially predictable, with previous studies highlighting temperature and rainfall as important factors in promoting emergence (Davidson 1934, Wallace 1967. We examined the relationship of these climatic factors with S. viridis emergence observed in this study and compared this relationship with historical data sets.…”
Section: Methodsmentioning
confidence: 96%
“…Previous studies have consistently found two peak abundance periods that result from autumn emergence of the Þrst generation and then from favorable spring conditions (Davidson 1934, Wallace 1967, Bishop et al 2001a). However, considerable variation has been observed for the number of generations that occur, with between three and Þve relatively distinct generations reported (Davidson 1934, Wallace 1967, Bishop et al 2001a).…”
mentioning
confidence: 88%
See 2 more Smart Citations